MATERNITY AND DOMESTIC WORK: HOW MUCH IS CARE WORTH? ANALYSIS FROM THE FEMINIST THEORY OF LAW - Macedo Rego, Julyana; Orlando Fernandes, Sabrinna; Martins de Paula, Helga Maria (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2022)
The sexual division of labor associates motherhood with an act of love, and, therefore, the activities carried out by mothers in caring for their children are not quantified, and therefore, they end up being disregarded when calculating the food to be paid to the mother. child by the other parent. In view of this, the present research proposes to analyze this phenomenon, based on the theory of invisible capital invested in motherhood, by the feminist jurist Ana Lúcia Dias. In order to achieve the proposed objective, the bibliographic review was adopted as a method.
Keywords: Maternity. Housework. Caution. Foods.